The phylogenetic relationships of Torrendiella and Hymenotorrendiella gen. nov. within the Leotiomycetes - Johnston, Peter; Park, Duckchul; Baral, Hans-Otto; Galán, Ricardo; Platas, Gonzalo; Tena, Raúl (Phytotaxa, 2014)
Morphological and phylogenetic data are used to revise the genus Torrendiella. The type species, described from Europe, is retained within the Rutstroemiaceae. However, Torrendiella species reported from Australasia, southern South America and China were found to be phylogenetically distinct and have been recombined in the newly proposed genus Hymenotorrendiella. The Hymenotorrendiella species are distinguished morphologically from Rutstroemia in having a Hymenoscyphus-type rather than Sclerotinia-type ascus apex. Zoellneria, linked taxonomically to Torrendiella in the past, is genetically distinct and a synonym of Chaetomella.